2015
DOI: 10.1007/s10495-015-1093-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipid rafts and estrogenic signalling: a functional role in the modulation of cell homeostasis

Abstract: It has become widely accepted that along with their ability to directly regulate gene expression, estrogens also influence cell signalling and cell function via rapid membrane-initiated events. Many of these signalling processes are dependent on estrogen receptors (ER) localized to the plasma membrane. However, the mechanisms by which ER are able to trigger cell signalling when targeted to the membrane surface have to be determined yet. Lipid rafts seem to be essential for the plasma membrane localization of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…33, 34 It is therefore of interest that ER α associates with lipid rafts where it is suggested to regulate cellular signalling. 35 It will be interesting to determine if BASP1 also has a role in this ER α function and if this is connected with the nuclear events that we report here.…”
Section: Discussionmentioning
confidence: 81%
“…33, 34 It is therefore of interest that ER α associates with lipid rafts where it is suggested to regulate cellular signalling. 35 It will be interesting to determine if BASP1 also has a role in this ER α function and if this is connected with the nuclear events that we report here.…”
Section: Discussionmentioning
confidence: 81%
“…The centre of order peak in the double Gauss distribution was significantly increased from 0.346 ± 0.006 to 0.378 ± 0.008 ( Figure 4G), indicating that β-estradiol could effectively change the membrane phase from Ld phase to Lo phase. The results indicated that the plasma membrane could preferentially recruit proteins and lipids to generate the rafts domains and then further affect their lipids diffusion [3,6,17]. The results indicated that the plasma membrane could preferentially recruit proteins and lipids to generate the rafts domains and then further affect their lipids diffusion [3,6,17].…”
Section: The Effect Of β-Estradiol On the Membrane Rafts In Mcf-7 Cmentioning
confidence: 97%
“…The β-estradiol could enhance the association of oestrogen receptors with the membrane rafts and induce rapid phosphorylation to trigger the nuclear receptor coactivator [5,6]. Herein, the membrane phase and lipid The effect of β-estradiol on membrane phase were visualised through GP imaging ( Figure 4A,B).…”
Section: The Effect Of β-Estradiol On the Membrane Rafts In Mcf-7 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they can act as catalytic domains where molecular interactions can be facilitated and contribute to the triggering of signaling cascades involved not only in apoptosis, but also in proliferation, differentiation, stress responses, necrosis, inflammation, autophagy, and senescence. In particular, the work by Maselli et al [9] describe how the so-called non-nuclear receptors for estrogen are embedded in lipid rafts and can serve as a cell membraneinitiated events providing a prompt response and activating survival intracellular pathways such as autophagy. This Issue is thus devoted to the analysis of different aspects underlying the implication of sphingolipids and lipid microdomains in cell pathophysiology: from their synthesis and assembly to their metabolic pathways and to their impact either on cell death by apoptosis or in autophagic process.…”
Section: Introductionmentioning
confidence: 99%